Atherectomy Techniques: Rotablation, Orbital and Laser - Sophia Khattak; Harish Sharma; Sohail Q Khan (Interventional Cardiology: Reviews, Research, Resources)
Coronary artery disease remains the leading cause of morbidity and mortality worldwide despite advancements in percutaneous coronary intervention (PCI). With an increasing ageing population, there is a significant challenge in addressing severe calcification in atherosclerotic plaque during angioplasty. This review article focuses on atherectomy strategies such as rotational atherectomy (RA), orbital atherectomy (OA) and excimer laser coronary angioplasty (ELCA) aimed at modifying calcified lesions and improving PCI outcomes. RA modifies plaque through rotational ablation, OA uses eccentrically mounted diamond-coated crown and has a reduced entrapment risk compared to RA. ELCA uses pulsatile laser energy to precisely ablate plaque tissue. This review provides insights into the mechanisms, procedural techniques and clinical outcomes associated with these calcium modification techniques. The selection of appropriate devices and adequate training are crucial for optimising lesion modification and enhancing procedural success. Further research and standardised protocols are required to overcome challenges associated with using these devices and expand their usage in clinical practice.